Draft genome sequences of 64 type strains of 50 species and 25 subspecies of the genus staphylococcus rosenbach 1884 - Cole, K; Foster, D; Russell, J; Golubchik, T; Llewelyn, M; Wilson, D; Crook, D; Paul, J; Modernising Medical Microbiology Consortium (American Society for Microbiology, 2019)
Members of the genus Staphylococcus have been isolated from humans, animals, and the environment. Accurate identification with whole-genome sequencing requires access to data derived from type strains. We provide sequence data for type strains of 64 taxa in the genus that at the time of this writing have standing in the nomenclature.